Analysis on Crown Health Assessment of Fabaceae in Bogor Botanical Garden - Erianto Indra Putra; Lutfi Ranggawuni Nugraha; Hendra Helmanto; Arief Noor Rachmadiyanto; Usman Usman; Lufthi Rusniarsyah; Andi Sukendro (Jurnal Silvikultur Tropika, 2023)
Bogor Botanical Garden (KRB) is an ex-situ plant conservation area with many plant types that dominated by tree. One of the family of trees collected in KRB is the Fabaceae family. This research aims to estimate the level of crown health condition in Fabaceae family in KRB using forest health monitoring (FHM) method. A total of 44 trees were observed using crown condition parameters to gain the visual crown rating (VCR), crown size index (CSI), and crown damaged index (CDI). This research showed that Fabaceae family in KRB reveal the VCR score of 6, indicated the medium health crown condition of tree. Thus, this research shows that most of the Fabaceae family’s tree at KRB are categorized in medium crown damaged rate. Keywords: Crown damaged index, crown health condition, crown size index, forest health monitoring, visual crown rating